APTAMERS ARE NEW PHARMACOLOGICAL SUBSTANCES FOR THE DEVELOPMENT OF ANTICOAGULANTS - A. V. Mazurov; V. A. Spiridonova («REMEDIUM GROUP» Ltd., 2017)
A ptamers are a new class of oligonucleotide compounds capable of specific binding to various molecular targets and inhibiting their activity. Aptamers are selected from a library of randomly syn-thesized oligonucleotides (from 20 to 60 nucleotides long) based on their ability to bind to the target molecule. In the future, such primary aptamers can be chemically modified to optimize their structure and increase stability. Aptamers are considered to be chemical (oligonucleotide) analogues of monoclonal antibodies: their specificity is similar to that of antibodies, and they have high affinity to their targets. Aptamers are widely used to create pharmacological medicines. As pharmacological substances, they have a number of benefits over antibodies and other protein molecules. Aptamers are practically non-immunogenic, chemically synthesized without the use of biological producers, and their antidotes can easily be created using complementary sequences. The review highlights reports devoted to the development of new anticoagulant aptamer-based medications. The most detailed studies, both preclinical and clinical (various phases of clinical trials), were performed in relation to the study of aptamers against vWF, factor IX and thrombin.